2018
DOI: 10.1186/s13071-018-2726-7
|View full text |Cite
|
Sign up to set email alerts
|

Ticks are more suitable than red foxes for monitoring zoonotic tick-borne pathogens in northeastern Italy

Abstract: BackgroundNortheastern Italy is a hotspot for several tick-borne pathogens, transmitted to animals and humans mainly by Ixodes ricinus. Here we compare the results of molecular monitoring of ticks and zoonotic TBPs over a six-year period, with the monitoring of red foxes (Vulpes vulpes) in an endemic area.ResultsIn the period 2011–2016, 2,578 ticks were collected in 38 sites of 20 municipalities of Belluno Province. Individual adults (264), pooled larvae (n = 330) and nymphs (n = 1984) were screened for tick-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 57 publications
1
18
1
Order By: Relevance
“…Lower prevalence has been detected in Spain (40), Germany (41), Hungary (42) and Slovakia (43) (72.2, 46.4, 20, and 9.7%, respectively). In Italy, previous findings have showed variable results depending on the geographical area, ranging from <1 to 54% (21)(22)(23)44). Most of the foxes in the present study were found to be infected with B. vulpes, as already reported in Spain (45), Italy (46), Croatia (47), Germany (41), Portugal (39), and Austria (31).…”
Section: Discussionsupporting
confidence: 65%
“…Lower prevalence has been detected in Spain (40), Germany (41), Hungary (42) and Slovakia (43) (72.2, 46.4, 20, and 9.7%, respectively). In Italy, previous findings have showed variable results depending on the geographical area, ranging from <1 to 54% (21)(22)(23)44). Most of the foxes in the present study were found to be infected with B. vulpes, as already reported in Spain (45), Italy (46), Croatia (47), Germany (41), Portugal (39), and Austria (31).…”
Section: Discussionsupporting
confidence: 65%
“…Even though wild carnivores have been incriminated as sentinels for Anaplasmataceae agents in natural environments, as well as in degraded and periurban areas ( 29 , 31 ) emphasized that the molecular screening of TBPs in vector ticks represents a more efficient system than the screening of foxes as sentinel animals in the specific epidemiological context of northeastern Italy (Belluno Province). Despite the detection of A. phagocytophilum and “ Candidatus Neoehrlichia mikurensis” in Ixodes ricinus nymphs and adults, all sampled foxes ( n = 97) were negative to Anaplasmataceae agents.…”
Section: Implications Of Anaplasmataceae Infection In Wild Carnivoresmentioning
confidence: 99%
“…Babesia-species members are globally recognized for their huge damages that they cause to the world industries of herds (2). Babesiosis is a tick-borne disease that generates a blood-based disease in different animals such as cows (3). Different genera and species of ticks such as Hyalomma and Rhipicephalus are well-known for their enhancement to transmit Babesia species to different animals (4).…”
Section: Introductionmentioning
confidence: 99%